MALDI imaging mass spectrometry of β‐ and γ‐crystallins in the ocular lens. (5th December 2019) - Anderson, David M.; Nye‐Wood, Mitchell G.; Rose, Kristie L.; Donaldson, Paul J.; Grey, Angus C.; Schey, Kevin L.
Abstract: Lens crystallin proteins make up 90% of expressed proteins in the ocular lens and are primarily responsible for maintaining lens transparency and establishing the gradient of refractive index necessary for proper focusing of images onto the retina. Age‐related modifications to lens crystallins have been linked to insolubilization and cataractogenesis in human lenses. Matrix‐assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) has been shown to provide spatial maps of such age‐related modifications. Previous work demonstrated that, under standard protein IMS conditions, α‐crystallin signals dominated the mass spectrum and age‐related modifications to α‐crystallins could be mapped. In the current study, a new sample preparation method was optimized to allow imaging of β‐ and γ‐crystallins in ocular lens tissue. Acquired images showed that γ‐crystallins were localized predominately in the lens nucleus whereas β‐crystallins were primarily localized to the lens cortex. Age‐related modifications such as truncation, acetylation, and carbamylation were identified and spatially mapped. Protein identifications were determined by top‐down proteomics analysis of lens proteins extracted from tissue sections and analyzed by LC‐MS/MS with electron transfer dissociation. This new sample preparation method combined with the standard method allows the major lens crystallins to be mapped by MALDI IMS.